Bioinspired cobalt cubanes with tunable redox potentials for photocatalytic water oxidation and CO2 reduction - Luo, Zhishan; Hou, Yidong; Zhang, Jinshui; Wang, Sibo; Wang, Xinchen (Beilstein Journal of Organic Chemistry, 2018)
The development of efficient, robust and earth-abundant catalysts for photocatalytic conversions has been the Achilles’ heel of solar energy utilization. Here, we report on a chemical approach based on ligand designed architectures to fabricate unique structural molecular catalysts coupled with appropriate light harvesters (e.g., carbon nitride and Ru(bpy)32+) for photoredox reactions. The “Co4O4” cubane complex Co4O4(CO2Me)4(RNC5H4)4 (R = CN, Br, H, Me, OMe), serves as a molecular catalyst for the efficient and stable photocatalytic water oxidation and CO2 reduction. A comprehensive structure–function analysis emerged herein, highlights the regulation of electronic characteristics for a molecular catalyst by selective ligand modification. This work demonstrates a modulation method for fabricating effective, stable and earth-abundant molecular catalysts, which might facilitate further innovation in the function-led design and synthesis of cubane clusters for photoredox reactions.
Keywords: CO2 reduction; cobalt cubane; photocatalysis; water oxidation; water splitting